Individualization, Differentiation and Interactivity - Paradigms of Effective Learning - Adriana Denisa Manea; Cristian Stan; Ion Albulescu (Babes-Bolyai University, 2023)
Centering on the student in the context of the instructional-educational action is achieved by generating both interactive/collaborative and differentiated/individualized learning situations, all the more so as the appropriate technological resources can be exploited to provide the feedback necessary for adjustment in learning. The present study presents an investigative analysis to decipher the understanding of the concepts of didactic and exploitative individualization, differentiation and interactivity, with the aim of identifying the contribution of differentiation/individualization and interactivity in achieving effective learning. The study revealed a common perception of the concepts of individualization, differentiation and interactivity at the level of teachers for preschool, primary and secondary education. Also, the academic performance of students in pre-university education (preschool, primary and secondary school) was influenced by interactive strategies and learning tasks based on individualization and differentiation to a comparative extent with their contribution to the development of the degree of socialization and positive interaction, of increasing the level social-emotional skills.